If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19 = -2(5x) + 7 Remove parenthesis around (5x) 19 = -2 * 5x + 7 Multiply -2 * 5 19 = -10x + 7 Reorder the terms: 19 = 7 + -10x Solving 19 = 7 + -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. 19 + 10x = 7 + -10x + 10x Combine like terms: -10x + 10x = 0 19 + 10x = 7 + 0 19 + 10x = 7 Add '-19' to each side of the equation. 19 + -19 + 10x = 7 + -19 Combine like terms: 19 + -19 = 0 0 + 10x = 7 + -19 10x = 7 + -19 Combine like terms: 7 + -19 = -12 10x = -12 Divide each side by '10'. x = -1.2 Simplifying x = -1.2
| (x-1)=-3 | | 5(3+5)= | | 13=5-8p | | -27+20o=73 | | 3w+3=-2(w-9) | | 12-5p=-48 | | 4x^6y^3+32y^3= | | 11a-30=-8 | | 4-3l=43 | | -4=4(x-6)+6x | | 8x-(3x+10)=95 | | 8=5+w | | 4x+25-2x-25=6 | | ((3x-5y)+2x)*2=3+3y(6x+4-8) | | 5-6(1-2x)=95 | | 15=19+-3k+-31 | | ((3x-5x)+2x)*2=3+3y(6x+4-8) | | 142-3x=33x+18 | | 4(2m-3)+2(3m-5)= | | ((3x-5x)+2x)*2=3+(6x+4-8) | | 7-8x=197-43x | | 3x-5x+2x*2=3+6x+4-8 | | 10-2(11x-5)= | | w^2-16w+64=0 | | 2x+4=59 | | 2|x|+4=59 | | 8ab^2+10ab-3b^2=0 | | 8ab^2+10ab-3b^2=(2a+3b) | | -2x-13=8x+1 | | 3.24x+7.14=5.34x | | -27x=27 | | -11x=18.7 |